Effects of lead (Pb) on Jatropha curcas L. growth under hydroponic conditions - Palchetti, Enrico; Grassi, Chiara; Masoni, Alberto; Zubieta, Claudia Gabriela; Valenzi, Elena; Whittaker, Anne; Benedettelli, Stefano; Vecchio, Vincenzo (Journal of Agriculture and Environment for International Development (JAEID), 2016)
The contamination of the environment with pollutants, like heavy metals from human activity, has caused the loss of agricultural land. One possible solution could be the utilization of phytoremediation technique with particular plant, capable of absorbing the contaminants from soil. Jatropha curcas, an important plant for the biodiesel production, in particular in tropical areas, has the capacity to grown in marginal land, compromised for food cultivation. The experiment was conducted in hydroponic conditions with the objective to evaluate the response and growth parameters of juvenile plants grown in presence of different Pb levels (0-100-200 mg/L). It was possible to study the interaction in the plant between some mineral element (Ca, Mg, Zn and Fe) and morphological parameters and Pb, and evaluate some tolerance indicators. Results showed that the plants were able to grow in presence of Pb and to accumulate high levels of heavy metal in the roots, followed by the stems and leaves. However, Jatropha curcas subjected to Pb treatment demonstrated stunted growth and alterations in mineral elements contents. The results suggest that J. curcas may tolerate the levels of Pb imposed, but there is low translocation of heavy metal to aerial tissues, within the time period of analysis.